APERSEPSI MAHASISWA TERHADAP VISI BERBUDAYA SANTRI DI UNIVERSITAS HAMZANWADI - Zainul Fikri; Abdullah Muzakar; Robyan Endru Bafadal (Universitas Hamzanwadi, 2020)
This study aims to determine students' perceptions of the cultured vision of students at Hamzanwadi Selong University. The approach used by researchers in this study is a qualitative descriptive approach, in this case, the researcher will describe the problems that occur to students regarding student perceptions of the cultured vision of students at Hamzanwadi University. Data collection techniques used are the method of observation (observation), interviews, and documentation. Then the data from the data collection results were analyzed descriptively and interpreted against the data. Students' perceptions of the cultured vision of students at Hamzanwadi University were that the character of students was still not formed due to a lack of knowing what the santri culture was like. The differences that occur in students have not been seen from the first time they enter, student responses related to the cultured vision of students are still seen as a slogan and view it as a psychic. The impact of the vision of the santri culture on students can be divided into two, namely constructive and destructive. And the constructive point is to make students religious and gain insight into the culture of the students. And the destructive aspect is that students only speak, not apply it, and the cultural vision of the santri is only regarded as a formality.